Supplementation with Oral Vitamin C Prior to and during Myeloablative Chemotherapy and Autologous Haematopoietic Stem Cell Transplantation: A Pilot Study - Anitra C. Carr; Emma Vlasiuk; Masuma Zawari; Natalie Meijer; Carolyn Lauren; Sean MacPherson; Jonathan Williman; Stephen T. Chambers (MDPI AG, 2022)
Chemotherapy-related side effects are common in patients undergoing myeloablative chemotherapy and haematopoietic stem cell transplantation. Some, such as oral mucositis, are believed to be due to enhanced oxidative stress and inflammation. Vitamin C, a potent antioxidant with anti-inflammatory properties, becomes severely depleted following myeloablative chemotherapy. The aim of our study was to assess the feasibility and efficacy of oral vitamin C supplementation to restore and maintain adequate vitamin C concentrations in patients undergoing myeloablative chemotherapy and stem cell transplantation. We carried out a pilot randomized controlled trial in 20 patients with myeloma and lymphoma. Placebo or vitamin C tablets (1 g twice daily) were initiated one week prior to transplantation and continued for 4 weeks post-transplantation. Blood samples were collected weekly for analysis of plasma vitamin C concentrations using high-performance liquid chromatography. The patients' symptoms and quality of life parameters were monitored using the World Health Organization oral toxicity scale and the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ). Pre-supplementation with oral vitamin C doubled vitamin C concentrations relative to placebo by day 0 (median 61 vs. 31 µmol/L), with 60% of those in the vitamin C group achieving concentrations ≥ 50 µmol/L, compared with only 10% in the placebo group. Following chemotherapy and transplantation, significance between the vitamin C and placebo groups was lost by day 7, with only 30% of the patients in the vitamin C group having plasma concentrations ≥ 50 µmol/L. This was partly due to intolerance of the oral intervention due to nausea/vomiting and diarrhoea (40% of the participants in each group). Oral mucositis was also observed in 40% of the participants at day 7 or 14. Overall, our study showed that whilst short-term oral vitamin C pre-supplementation was able to restore adequate vitamin C status by day 0, ongoing supplementation could not maintain adequate vitamin C concentrations following chemotherapy and transplantation. Thus, intravenous vitamin C should be trialled as this bypasses the gastrointestinal system, negating intolerance issues and improving bioavailability of the vitamin.